2019
DOI: 10.4236/jct.2019.105029
|View full text |Cite
|
Sign up to set email alerts
|

HPV18 E6 and E7 Intratumour Heterogeneity in Esophageal Cancer

Abstract: The development of esophageal cancer accompanied by the presence of human papillomavirus (HPV) DNA into the host genome. By evaluating the expression of this virus for tumor cell origin and also their cell grows and migrations, we examined esophageal cancer clonality in the context of intra-tumor heterogeneity. In this research, we have checked the expression of HPV18 E6 and E7 in different single cell clones by the manual cell picking method in the HPV positive esophageal cancer (EC109), EC109 cell line used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…We have reported similar observations for a HPV18 E6-induced effect, in which only a subset of the cell population co-expressing E6 and activated Ras were transformed to cancer-like cells and those were the cells that expressed higher levels of E6 oncogene [ 49 ]. Single-cell clone analysis of HPV18 E6 and E7 positive human esophageal cancer cells also showed that the intra-tumor heterogeneity is due to variation in the level of E6 and E7 expression, with cells expressing higher levels exhibiting cell proliferation and invasive behavior [ 89 ]. Hence, the Drosophila model could be a valuable in vivo system for understanding the mechanisms underlying the intra-tumor genetic heterogeneity, which is currently a great problem in the treatment of cancers including HPV-associated cancers [ 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have reported similar observations for a HPV18 E6-induced effect, in which only a subset of the cell population co-expressing E6 and activated Ras were transformed to cancer-like cells and those were the cells that expressed higher levels of E6 oncogene [ 49 ]. Single-cell clone analysis of HPV18 E6 and E7 positive human esophageal cancer cells also showed that the intra-tumor heterogeneity is due to variation in the level of E6 and E7 expression, with cells expressing higher levels exhibiting cell proliferation and invasive behavior [ 89 ]. Hence, the Drosophila model could be a valuable in vivo system for understanding the mechanisms underlying the intra-tumor genetic heterogeneity, which is currently a great problem in the treatment of cancers including HPV-associated cancers [ 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%